INNOVATIVE APPROACHES TO PROJECT MANAGEMENT: FROM AGILE METHODOLOGIES TO INTEGRATED ENVIRONMENTAL PRODUCTION STRATEGIES - Dobizha, Nataliia; Pohrishchuk, Borys; Pohrishchuk, Oleh (Current Problems of Sustainable Development, 2026)
The article is devoted to the analysis of modern innovative project management approaches to the production environment, which combine flexible methodologies and environmentally friendly approaches. The features of the implementation of Agile, Lean, Kanban and Scrum systems in the context of dynamic production focused on sustainable development are considered. The paper identifies key methodological elements that ensure flexibility, adaptability and reduction of resource dependence of production processes. Particular attention is paid to the practical case of the Wood Trick company, which specializes in the manufacture of 3D wooden designers and demonstrates an example of the successful integration of digital technologies, eco-oriented thinking and flexible management. A structural assessment of the company’s internal project model is carried out, in particular the use of Kanban logic, CAD tools, Kaizen practices and Lean quality control. The relationship between the implementation of iterative management cycles and increased environmental efficiency, reduced production waste and increased brand value orientation is analyzed. The conclusion is made about the feasibility of scaling combined management strategies to small and medium-sized businesses, taking into account the ecosystem approach and sustainable design of production systems.
Keywords: flexible management; Kanban; Lean production; ecological production; project management; Wood Trick; innovative models; Agile; sustainable development; CAD modeling